Chads, foids, and blackpills - Krüger, Thomas Ian (Rhodes University, 2026)
The present research focuses on understanding the language and interactions between incel members on the website incels.is. In broad strokes, the research question is to ask; what is the nature and content of online, textual interactions in ‘incel’ communities and interactive spaces? Previous research has demonstrated this as a hateful group of men who express violence and, in some cases, enact violence. The present research adds to this effort by developing an analysis of ‘incel discourse’ which can be used to identify incel language in online spaces. Furthermore, this is important because understanding how one kind of masculinity is perpetuated within online spaces helps understand how Gender-based violence is perpetuated through this language. While the present research does not look at a novel concept, it does apply a new lens and focus through the use of a Foucauldian discourse analysis. The important thread of incel discourse starts in a strong belief in biological reductionism, which incels use to justify their subhuman status. Through this subhuman status, incel members develop a ‘coping’ discursive theme as well as extreme misogyny because they are angry that they feel as though they are subhuman. Within incel discourse, they demonstrate identity management strategies through their discussions of intelligence and rationality while policing their boundaries through a membership discursive theme. This adds to the current literature and aids the goal of eventually dismantling this harmful ideology that has and likely will continue to contribute to real world violence.
a Foucauldian discourse analysis of interactions on the website incels.is
Keywords: Uncatalogued